Economic adjustment : policies and problems : papers presented at a seminar held in Wellington, New Zealand, February 17-19, 1986 - Holmes, Frank; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1987)
This book deals with policies and problems associated with interdependence among the region's economies
Includes bibliographical references.
oo 18/10/2018
Loans
Keywords: Economic policy; Oceania; Korea (South); New Zealand